IoT system for anytime/anywhere monitoring and control of vehicles' parameters - Ferreira, J.; Pedrosa, D.; Martins, A. (2017 IEEE International Conference on Service Operations and Logistics, and Informatics, SOLI 2017, 2017)
This paper presents an IoT (Internet of Things) system designed to allow the monitoring and control of parameters of the users’ vehicles, anytime and anywhere in the world, through the Internet. The system prototype was developed and tested using an electric vehicle (EV) and the respective sensor systems. The main components of the proposed IoT system are: a Bluetooth Low Energy (BLE) intra-vehicular wireless sensor network (IVWSN); a mobile device that acts both as the vehicle’s gateway, connecting the IVWSN to the Internet, and as the vehicle’s human machine interface (HMI); an online server/database, based on Firebase; a client, which can be either a mobile device or a personal computer; and a residential wireless sensor network (WSN). The use of a wireless network to collect sensor data inside of the vehicle introduces some advantages when compared with conventional wired networks, whereas the inclusion of a residential WSNs in the proposed IoT architecture allows the provision of additional features, such as automatic control of the EV battery charging process. Experimental results are provided to assess the performance of the developed IVWSN and HMI